An outbreak after all: Cutibacterium acnes among pediatric patients with cerebrospinal fluid diversion device infections highlights gaps in guidelines - Felicia Scaggs Huang; Cameron Griffin; Matthew Fenchel; Melanie DuBose; Andrea Ankrum; Joshua K. Schaffzin (Cambridge University Press, 2024)
Abstract Objective: Cutibacterium acnes is normal skin flora but can cause sterile implant infections. We investigated a cluster of seven patients with C. acnes in anaerobic cerebrospinal fluid (CSF) cultures in November 2020. Further analysis identified a missed outbreak, highlighting ambiguity in diagnosis of indolent organisms in the 2017 IDSA meningitis guidelines. Design: Outbreak investigation. Setting: Quaternary pediatric facility. Patients: A case was defined as a hospitalized patient with C. acnes isolated from CSF culture from January 1, 2016 to December 31, 2022. Methods: We defined comparison periods based on timing of C. acnes culture positivity as 1) pre-outbreak (2016-2020), 2) outbreak (2020-2021), and 3) post-outbreak (2022). Rates of C. acnes positive cultures per 1000 CSF cultures and rate ratios were calculated by comparison periods. Results: We identified 9 positive C. acnes CSF cultures among 7 cases November 10-27, 2020, all with at least 1 CSF diversion device. The anaerobic culture media was substituted at the time of case cluster. In 2021, the culture media was implemented permanently with no increase in C. acnes culture positivity. The rate of C. acnes positive CSF cultures and rate ratio increased in the outbreak period (p=0.01) compared to pre-outbreak and post-outbreak periods. There was no difference between the pre- and post-outbreak periods. Conclusions: Retrospective analysis of CSF culture data led to reclassifying a C. acnes pseudo-outbreak as a true outbreak in CSF diversion devices at our institution. Clearer guidance is needed to delineate the role of C. acnes in CSF diversion device infections.